Family Loneliness: Its Effects in the Development of Empathy, Teamwork and Lifelong Learning Abilities in Medical Students - Berduzco-Torres, Nancy; Medina, Pamela; Choquenaira-Callañaupa, Begonia; San-Martín, Montserrat; Delgado Bolton, Roberto C.; Vivanco, Luis (Frontiers in Psychology, 2020)
Context: Family offers an important source of social support where individuals acquire social abilities that are necessary to create positive human relationships. This influence has been discussed by different sociological and psychological theories along the lifespan of individuals. In medicine, empathy, teamwork and lifelong learning have been described as specific elements of professionalism that have special importance in the interaction with patients and in physicians’ wellbeing at the workplace. This study was performed with the aim of demonstrating the following hypothesis: in the absence of specific training in empathy and teamwork and lifelong learning abilities, their development in medical students is associated with the students’ perception of loneliness from their family environment Methods: A cross-sectional study was performed in the only two medical schools of Cusco (Peru), one private and the other public. Jefferson Scales of Empathy, Teamwork and Lifelong Learning were used as main measures. Mother-son and father-son relationships and family loneliness were measured to characterize the family environment. In addition, information related to sex, medical school, academic achievements, and place of origin were collected to control possible biases. Comparative, correlation and multiple regression analyses were performed among the variables studied. Results: In a sample of 818 medical students, differences by school appeared in empathy, teamwork, lifelong learning, and family loneliness. In addition, family loneliness showed an inverse correlation with empathy, teamwork and learning measures. While having a positive relationship with the mother was associated with a greater development of empathy and learning abilities in the entire sample, a similar effect was observed in father-son relationships but only in the private medical school group. Finally, in the public medical group, a multiple regression model explained 43% of the variability of empathy based on a lineal relationship with teamwork (p<0.001), learning (p<0.001) and family loneliness (p<0.001). Conclusions: These findings confirm how family loneliness is detrimental for the development of medical professionalism. Also, they support the important role that family, and especially parents, play in the development of empathy, teamwork and learning abilities in medical students. Finally, these findings highlighted important differences among students enrolled in public and private medical schools.